2013
DOI: 10.1089/ars.2012.4615
|View full text |Cite
|
Sign up to set email alerts
|

p53 Orchestrates the PGC-1α-Mediated Antioxidant Response Upon Mild Redox and Metabolic Imbalance

Abstract: Aims: The transcriptional coactivator peroxisome proliferator-activated receptor-c coactivator-1 a (PPARGC1A or PGC-1a) is a powerful controller of cell metabolism and assures the balance between the production and the scavenging of pro-oxidant molecules by coordinating mitochondrial biogenesis and the expression of antioxidants. However, even though a huge amount of data referring to the role of PGC-1a is available, the molecular mechanisms of its regulation at the transcriptional level are not completely und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
187
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 177 publications
(193 citation statements)
references
References 49 publications
5
187
0
1
Order By: Relevance
“…In particular, caloric restriction increases both eNOS and nNOS activity (Nisoli et al, 2005;Fusco et al, 2012). In our laboratory, we have shown that, in skeletal muscle, caloric restriction also increases NO bioavailability independently of NOS upregulation (Aquilano et al, 2013a). In particular, caloric restriction reduces the level of GSH, the main intracellular NO buffer (Aquilano et al, 2011a;Aquilano et al, 2011b;Baldelli et al, 2008).…”
Section: Pgc-1a and No In The Regulation Of Oxidative Stressmentioning
confidence: 84%
See 1 more Smart Citation
“…In particular, caloric restriction increases both eNOS and nNOS activity (Nisoli et al, 2005;Fusco et al, 2012). In our laboratory, we have shown that, in skeletal muscle, caloric restriction also increases NO bioavailability independently of NOS upregulation (Aquilano et al, 2013a). In particular, caloric restriction reduces the level of GSH, the main intracellular NO buffer (Aquilano et al, 2011a;Aquilano et al, 2011b;Baldelli et al, 2008).…”
Section: Pgc-1a and No In The Regulation Of Oxidative Stressmentioning
confidence: 84%
“…In particular, caloric restriction reduces the level of GSH, the main intracellular NO buffer (Aquilano et al, 2011a;Aquilano et al, 2011b;Baldelli et al, 2008). The resulting increased NO bioavailability is the genuine mediator of the upregulation of PGC-1a, which, in turn, favours the expression of antioxidant proteins SOD2 and c-GCS (also known as glutamate cysteine ligase) (Aquilano et al, 2013a).…”
Section: Pgc-1a and No In The Regulation Of Oxidative Stressmentioning
confidence: 99%
“…p53 has been reported to be the modulator of oxidative stress-it downregulates low oxidative stress and exacerbates higher levels of stresses (22). For example, at low levels of oxidative stress, p53 activates antioxidant genes such as sestrin and glutathione peroxidase (1,6,16). Additionally, p53 induces the expression of TP53-induced glycolysis and apoptosis regulator, which slows glycolysis and promotes the production of NADPH to decrease ROS levels (50).…”
Section: Discussionmentioning
confidence: 99%
“…After treatment, oligonucleotide pulldown assay was carried out as described previously (40) by using the cAMP response element sequence on the mouse PGC-1␣ gene (ppargc1a) promoter (supplemental Table S1). Oligonucleotide pulldown specificity was demonstrated with mutant oligonucleotides used as negative controls (data not shown).…”
Section: Methodsmentioning
confidence: 99%